Prognostic impact of hemoglobin drop during hospital stay in patients with acute coronary syndromes - Nabais, S; Gaspar, A; Costa, J; Azevedo, P; Rocha, S; Torres, M; Álvares-Pereira, M (Sociedade Portuguesa de Cardiologia, 2009)
INTRODUCTION: Bleeding is currently the most common non-cardiac complication of therapy in patients with acute coronary syndromes (ACS), and may itself be associated with adverse outcomes. The aim of this study was to determine the effect of hemoglobin drop during hospital stay on outcome among patients with ACS. METHODS: Using Cox proportional-hazards modeling, we examined the association between hemoglobin drop and death or myocardial infarction (MI) at 6 months in 1172 patients admitted with ACS to an intensive cardiac care unit. Patients were stratified according to quartiles of hemoglobin drop: Q1, < or = 0.8 g/dL; Q2, 0.9-1.5 g/dL; Q3, 1.6-2.3 g/dL; Q4, > or = 2.4 g/dL. We also identified independent predictors of increased hemoglobin drop (> or =2.4 g/dL) using multivariate logistic regression analysis. RESULTS: Median nadir hemoglobin concentration was 1.5 g/dL lower (IQR 0.8-2.3) compared with baseline hemoglobin (p < 0.0001). Independent predictors of increased hemoglobin drop included older Sage, renal dysfunction, lower weight, and use of thrombolytic therapy, glycoprotein IIb/IIIa inhibitors, nitrates, and percutaneous coronary intervention. Higher levels of hemoglobin drop were associated with increased rates of 6-month mortality (8.0% vs. 9.4% vs. 9.6% vs. 15.7%; p for trend = 0.014) and 6-month death/ MI (12.4% vs. 17.0% vs. 17.2% vs. 22.1%; p for trend = 0.021). Using Q1 as reference group, the adjusted hazard ratio (HR) for 6-month mortality and 6-month death/MI among patients in the highest quartile of hemoglobin drop was 1.83 (95% confidence interval [CI] 1.08-3.11; p = 0.026) and 1.60 (95% CI 1.04-2.44; p = 0.031) respectively. Considered as a continuous variable, the adjusted HR for 6-month mortality was 1.16 (95% CI 1.01-1.32; p = 0.030) per 1 g/dL increase in hemoglobin drop. CONCLUSIONS: A decrease in hemoglobin frequently occurs during hospitalization for ACS and is independently associated with adverse outcomes.
Keywords: Hemoglobinas; Síndrome Coronária Aguda; Prognóstico